Legal Politics of Constitutional Complaint: Prospects for Implementation of the Indonesian Legal System - Agnes Fitryantica; Lita Tyesta Addy Listya Wardani; Ratna Herawati; Roqiyul Maarif Syam (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2026)
The concept of constitutional complaints is becoming increasingly crucial in the protection of fundamental rights. In Indonesia, the authority of the Constitutional Court (MK) is currently limited to reviewing laws, resolving election disputes, dissolving political parties, and resolving disputes over the jurisdiction of state institutions. Consequently, there is a legal vacuum in protecting the rights of citizens violated by actual acts or omissions of state officials that are not related to the constitutionality of laws. This article examines the legal politics behind the absence of constitutional complaints in Indonesia as well as the prospects for their implementation. Using a normative legal approach and comparative analysis with Germany, South Korea, and Thailand, this study explores the role of this instrument in safeguarding citizens’ rights, preventing abuse of power, and strengthening judicial independence. The research findings indicate that the adoption of constitutional complaints in Indonesia would expand access to justice, align the legal system with international human rights standards, and affirm the Constitutional Court’s role as the guardian of the constitution. Nevertheless, challenges such as political resistance, the risk of a surge in caseload, and institutional readiness must be addressed through careful design. The constitutional complaint is not merely a prospective legal reform but a constitutional necessity to realize a democratic, participatory, rights-based state and to strengthen public confidence in the rule of law.